2018
DOI: 10.5114/fn.2018.76615
|View full text |Cite
|
Sign up to set email alerts
|

The impact of bone marrow-derived mesenchymal stem cells on neovascularisation in rats with brain injury

Abstract: A b s t r a c tIntroduction: The impact of bone marrow-derived mesenchymal stem cells (BM-MSCs) on neovascularisation in rats with craniocerebral injury (CI) was investigated. Material and methods: The rate CI model was established by the free-fall method, and then rats were randomly divided into a transplanted group (EG) and a control group (CG). Rats in the transplanted group were injected with BM-MSCs in the lateral ventricle, while those in the control group were injected with normal saline. Modified neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…In treating TBI, re-establishing blood flow to the injured area is critical for cellular growth and recovery. Endothelial progenitor cells (EPCs) promote angiogenesis through tissue repair and can be mobilized under various stimulating factors, including vascular endothelial growth factor (VEGF) [34]. However, VEGF and other vascular growth factor levels are reduced following TBI [35].…”
Section: Mesenchymal Stem Cell Therapies For Tbimentioning
confidence: 99%
See 1 more Smart Citation
“…In treating TBI, re-establishing blood flow to the injured area is critical for cellular growth and recovery. Endothelial progenitor cells (EPCs) promote angiogenesis through tissue repair and can be mobilized under various stimulating factors, including vascular endothelial growth factor (VEGF) [34]. However, VEGF and other vascular growth factor levels are reduced following TBI [35].…”
Section: Mesenchymal Stem Cell Therapies For Tbimentioning
confidence: 99%
“…A multitude of studies have demonstrated that BMSCs have an angiogenic effect in promoting neurologic recovery in TBI animal models. Hu et al found that BMSC transplantation increased the number of EPCs in the peripheral blood of rats with TBI 24 hours after injury, which correlated with improved modified neurological severity scores (mNSS) compared to controls [34]. This effect was also investigated by Guo et al, who demonstrated that BMSCs administered intravenously post-TBI upregulated VEGF and angiogenin-1 levels in a rat controlled cortical impact (CCI) TBI model.…”
Section: Mesenchymal Stem Cell Therapies For Tbimentioning
confidence: 99%
“…Besides, inflammation and degeneration process in neurons lasts for years after TBI, causing chronic symptoms in TBI patients [13]. There is plenty of treatments for TBI nowadays, including traditional medicine treatment, transplanting neural stem cells (NSCs) and bone marrow-derived mesenchymal stem cells [14]. Among them, tetrahydroxystilbene glucoside (TSG) is extracted from traditional Chinese medicine, and has anti-atherosclerosis, hepatoprotective and hypolipidemic effects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that enhancing neurogenesis, angiogenesis, and immunoregulation by secreting chemokine and growth factors are involved in the functional recovery induced by stem cell/progenitor cell-based interventions. 96 99 Several clinical trials in cell-based treatment for TBI recovery have demonstrated safety of this therapeutic approach. 100,101 However, the administration route, dose, and time window still remain controversial.…”
Section: Therapeutic Studies In Animal Models Of Tbimentioning
confidence: 99%
“…MSCs were mainly isolated from the bone marrow, umbilical cord, and adipose tissue. 99,101,102 The administration dose of MSCs ranges from 0.1 to 20 million cells per kg body weight. 96 The approaches of lateral ventricle and intravenous injection have been utilized.…”
Section: Therapeutic Studies In Animal Models Of Tbimentioning
confidence: 99%